(Meth)acrylic polymer composition, pressure-sensitive adhesive sheet, and optical member
The (meth)acrylic polymer composition with specific molecular weight ratios and functional groups addresses coating breakage and adhesive layer cohesion issues, enabling high-speed application with improved processability and reduced blade adherence.
Patent Information
- Application Number
- JP2020181883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-10-29
AI Technical Summary
Conventional acrylic adhesives face issues with coating breakage and adhesive layer cohesion when applied at high speeds due to low molecular weight of (meth)acrylic polymers to reduce organic solvent content, leading to poor processability and increased sticking to cutting blades.
A (meth)acrylic polymer composition with a weight average molecular weight of 50,000 to 300,000 and a z+1 average molecular weight of 500,000 to 20 million, maintaining a ratio of z+1/Mw of 5.5 or more, along with the inclusion of hydroxyl and carboxy groups, is used to enhance coating properties and processability.
The composition achieves excellent coating properties and film formation with high solid content concentration, reducing adhesive layer adherence to cutting blades and ensuring good appearance and workability.
Smart Images

Figure 0007621088000001 
Figure 0007621088000002 
Figure 0007621088000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a (meth)acrylic polymer composition, a pressure-sensitive adhesive sheet, and an optical member. [Background technology]
[0002] In recent years, there has been a demand for environmentally friendly adhesives, and low-VOC (Volatile Organic Compounds) adhesives that contain a small amount of organic solvents have been attracting attention. For example, Patent Document 1 discloses a polymer solution that contains a (meth)acrylic polymer having a weight-average molecular weight of 300,000 or less and an organic solvent, has a viscosity of 1500 mPa s or less at 25°C, and has an organic solvent content of 20% by mass to 50% by mass, and is cured by exposure to ionizing radiation to form a pressure-sensitive adhesive layer. Patent Document 2 discloses an acrylic resin solution containing an acrylic resin (A) having a weight-average molecular weight of 50,000 to 300,000 and an organic solvent (B) in which the chain transfer constant of vinyl acetate to the organic solvent at 60°C is 250 or more and having a solid content concentration of 60 mass % or more, the acrylic resin solution being used for producing a non-active energy ray-curable, solvent-based acrylic pressure-sensitive adhesive. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-043184 A [Patent Document 2] JP 2011-246700 A Summary of the Invention [Problem to be solved by the invention]
[0004] In general, acrylic adhesives are prepared by mixing a polymer solution containing a (meth)acrylic polymer and an organic solvent with a crosslinking agent. In order to reduce the content of the organic solvent in conventional acrylic adhesives (in other words, to increase the solid content concentration), the weight-average molecular weight of the (meth)acrylic polymer must be reduced from the viewpoint of coating viscosity, as in the acrylic adhesives described in Patent Documents 1 and 2. However, if the weight-average molecular weight of the (meth)acrylic polymer is small, for example, when the acrylic adhesive is applied to a support at a high speed (for example, 50 m / min or more) for the purpose of increasing the productivity of the adhesive sheet, a problem may occur in that the coating film is interrupted. In addition, if the molecular weight of the (meth)acrylic polymer is simply reduced, the cohesive force of the adhesive layer formed is insufficient, and therefore, when the adhesive sheet is processed, a problem may occur in that adhesive substances originating from the adhesive layer adhere to a cutting blade.
[0005] An object of one embodiment of the present disclosure is to provide a (meth)acrylic polymer composition that exhibits excellent coatability even when the solid content is high, and is capable of forming a film having excellent processability. The problem to be solved by another embodiment of the present disclosure is to provide a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer that has a good appearance and excellent processability. Another problem to be solved by another embodiment of the present disclosure is to provide an optical member having a pressure-sensitive adhesive layer that has a good appearance and excellent processability. [Means for solving the problem]
[0006] Specific means for solving the problems include the following aspects. <1> A (meth)acrylic polymer composition comprising: a (meth)acrylic polymer having a weight average molecular weight (Mw) of 50,000 to 300,000, a z+1 average molecular weight (Mz+1) of 500,000 to 20 million, and a ratio (Mz+1 / Mw) of the z+1 average molecular weight (Mz+1) to the weight average molecular weight (Mw) of 5.5 or more; and an organic solvent. <2> The (meth)acrylic polymer has at least one of a hydroxyl group and a carboxy group. <1> The (meth)acrylic polymer composition according to claim 1. <3> The solid content is 40% by mass to 90% by mass. <1> or <2> The (meth)acrylic polymer composition according to claim 1. <4> Contains crosslinking agent <1> ~ <3> The (meth)acrylic polymer composition according to any one of the above items. <5> Used as an adhesive <1> ~ <4> The (meth)acrylic polymer composition according to any one of the above items. <6> <5> 2. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the (meth)acrylic polymer composition according to claim 1. <7> <5> 2. An optical member comprising a pressure-sensitive adhesive layer formed from the (meth)acrylic polymer composition according to claim 1. Effect of the Invention
[0007] According to one embodiment of the present disclosure, there is provided a (meth)acrylic polymer composition which exhibits excellent coatability even when the solid content concentration is high, and is capable of forming a film having excellent processability. According to another embodiment of the present disclosure, there is provided a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer that has good appearance and excellent processability. Furthermore, according to another embodiment of the present disclosure, there is provided an optical member having a pressure-sensitive adhesive layer that has good appearance and excellent processability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The (meth)acrylic polymer composition, the pressure-sensitive adhesive sheet, and the optical member of the present disclosure will be described in detail below. The following description of the requirements may be based on the representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.
[0009] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.
[0010] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when a plurality of substances corresponding to each component are present in the (meth)acrylic polymer composition, the amount of each component in the (meth)acrylic polymer composition means the total amount of the plurality of substances present in the (meth)acrylic polymer composition, unless otherwise specified.
[0011] In the present disclosure, "(meth)acrylic polymer" means a polymer in which the content of structural units derived from monomers having a (meth)acryloyl group is 50 mass% or more of all structural units (i.e., all structural units of the (meth)acrylic polymer). In the present disclosure, "(meth)acrylic monomer" means a monomer having a (meth)acryloyl group.
[0012] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".
[0013] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.
[0014] In the present disclosure, the terms "adhesive" and "adhesive composition" have the same meaning.
[0015] In the present disclosure, the "solid content" of the (meth)acrylic polymer composition means the components remaining after excluding the solvent from the (meth)acrylic polymer composition. In the present disclosure, the "solid content" of the (meth)acrylic polymer composition means the mass of the components excluding the solvent from the (meth)acrylic polymer composition. In the present disclosure, the "solid content concentration" of a (meth)acrylic polymer composition means the mass proportion of the solid content in the (meth)acrylic polymer composition (i.e., components excluding the solvent from the (meth)acrylic polymer composition). In this disclosure, "solvent" means water and organic solvents.
[0016] In the present disclosure, "excellent coatability" means the property of being able to satisfactorily form a coating film with good appearance even when coating is performed at high speed (e.g., 50 m / min or more). Here, "being able to satisfactorily form a coating film" means being able to form a coating film without interruption from the start to the end of coating.
[0017] [(Meth)acrylic polymer composition] The (meth)acrylic polymer composition of the present disclosure contains a (meth)acrylic polymer having a weight average molecular weight (Mw) of 50,000 to 300,000, a z+1 average molecular weight (Mz+1) of 500,000 to 20,000,000, and a ratio (Mz+1 / Mw) of the z+1 average molecular weight (Mz+1) to the weight average molecular weight (Mw) of 5.5 or more (hereinafter also referred to as a "specific (meth)acrylic polymer"), and an organic solvent. The (meth)acrylic polymer composition of the present disclosure exhibits excellent coatability even when the solid content concentration is high, and can form a film with excellent processability.
[0018] In recent years, VOC adhesives with a low content of organic solvents have been attracting attention as environmentally friendly adhesives. In general, acrylic adhesives are prepared by mixing a polymer solution containing a (meth)acrylic polymer and an organic solvent with a crosslinking agent. However, if the content of the organic solvent is reduced, the coating viscosity increases, so it becomes necessary to reduce the weight average molecular weight of the (meth)acrylic polymer. If the molecular weight of the (meth)acrylic polymer is reduced, the molecular chain becomes shorter, so that the entanglement between the (meth)acrylic polymers is reduced, and the entanglement is unraveled by a slight stress. For this reason, when an acrylic adhesive with a low molecular weight of the (meth)acrylic polymer is applied at high speed, the coating film may be broken. In addition, if the molecular weight of the (meth)acrylic polymer is simply reduced, the cohesive force of the adhesive layer formed is insufficient, so that when the adhesive sheet is processed, the adhesive material derived from the adhesive layer may adhere to the cutting blade. In contrast, the (meth)acrylic polymer composition of the present disclosure is characterized in that, in its design, the weight average molecular weight (Mw) of the (meth)acrylic polymer is kept within a relatively small specific range from the viewpoint of coating viscosity, while the (meth)acrylic polymer contains a specific proportion or more of a relatively large molecular weight within a specific range in order to improve coatability and processability by sufficient entanglement between the (meth)acrylic polymers. As a result, the (meth)acrylic polymer composition of the present disclosure exhibits excellent coatability even when the organic solvent content is low (in other words, when the solid content is high), and can form a film with excellent processability. For example, when used as a pressure-sensitive adhesive, a pressure-sensitive adhesive layer with excellent processability can be formed. For this reason, a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed by the (meth)acrylic polymer composition of the present disclosure is less likely to have a problem of adhesive matter originating from the pressure-sensitive adhesive layer adhering to a cutting blade during processing.
[0019] [Specific (meth)acrylic polymer] The (meth)acrylic polymer composition of the present disclosure contains a (meth)acrylic polymer [i.e., a specific (meth)acrylic polymer] having a weight average molecular weight (Mw) of 50,000 to 300,000, a z+1 average molecular weight (Mz+1) of 500,000 to 20,000,000, and a ratio (Mz+1 / Mw) of the z+1 average molecular weight (Mz+1) to the weight average molecular weight (Mw) of 5.5 or more.
[0020] The Mw of the specific (meth)acrylic polymer is 50,000 to 300,000. When the Mw of the specific (meth)acrylic polymer is 50,000 or more, a coating film tends to be formed well even when the solid content is high. From this viewpoint, the Mw of the specific (meth)acrylic polymer is 50,000 or more, preferably 80,000 or more, more preferably 100,000 or more, and even more preferably 120,000 or more. When the Mw of the specific (meth)acrylic polymer is 300,000 or less, there is a tendency that a coating film with good appearance can be formed even when the solid content concentration is high. From this viewpoint, the Mw of the specific (meth)acrylic polymer is 300,000 or less, preferably 280,000 or less, more preferably 250,000 or less, and even more preferably 220,000 or less.
[0021] The Mz+1 of the specific (meth)acrylic polymer is 500,000 to 20,000,000. When the Mz+1 of the specific (meth)acrylic polymer is 500,000 or more, a coating film tends to be formed well even when the solid content is high. From this viewpoint, the Mz+1 of the specific (meth)acrylic polymer is 500,000 or more, preferably 800,000 or more, more preferably 1,000,000 or more, and even more preferably 1,200,000 or more. When the Mz+1 of the specific (meth)acrylic polymer is 20 million or less, there is a tendency that a coating film with good appearance can be formed even when the solid content concentration is high. From this viewpoint, the Mz+1 of the specific (meth)acrylic polymer is 20 million or less, preferably 15 million or less, more preferably 10 million or less, and even more preferably 5 million or less.
[0022] The specific (meth)acrylic polymer has an Mz+1 / Mw ratio of 5.5 or more. When the Mz+1 / Mw of the specific (meth)acrylic polymer is 5.5 or more, a coating film tends to be formed well even when the solid content concentration is high. When the Mz+1 / Mw of the specific (meth)acrylic polymer is 5.5 or more, a film with excellent processability tends to be formed. When the (meth)acrylic polymer composition of the present disclosure is used as an adhesive, for example, an adhesive layer with excellent processability can be formed, and when an adhesive sheet having the adhesive layer is cut, the adhesive layer tends to be less likely to adhere to a cutting blade. From this viewpoint, the Mz+1 / Mw of the specific (meth)acrylic polymer is 5.5 or more, preferably 6.5 or more, more preferably 7.5 or more, even more preferably 8 or more, and particularly preferably 9 or more. The upper limit of Mz+1 / Mw of the specific (meth)acrylic polymer is not particularly limited, but is, for example, preferably 200 or less, more preferably 150 or less, even more preferably 100 or less, and particularly preferably 80 or less. When the Mz+1 / Mw of the specific (meth)acrylic polymer is 200 or less, for example, when the Mz+1 / Mw of the (meth)acrylic polymer is adjusted to a desired value by controlling the polymerization reaction of a monomer, the above control tends to become easier.
[0023] The specific (meth)acrylic polymer is preferably an embodiment in which Mw is 50,000 to 300,000, Mz+1 is 500,000 to 20 million, and Mz+1 / Mw is 5.5 to 200, more preferably an embodiment in which Mw is 80,000 to 280,000, Mz+1 is 800,000 to 15 million, and Mz+1 / Mw is 6.5 to 150, even more preferably an embodiment in which Mw is 100,000 to 250,000, Mz+1 is 1 million to 10 million, and Mz+1 / Mw is 7.5 to 100, and particularly preferably an embodiment in which Mw is 120,000 to 220,000, Mz+1 is 1.2 million to 5 million, and Mz+1 / Mw is 8 to 80.
[0024] The Mw and Mz+1 of the specific (meth)acrylic polymer are values determined by the following method, specifically, according to the following (1) to (3). (1) A solution of the specific (meth)acrylic polymer is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the specific (meth)acrylic polymer. (2) Using the film-like specific (meth)acrylic polymer obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the specific (meth)acrylic polymer to the sample solution. (3) Gel permeation chromatography (GPC) measurement is carried out under the following conditions, and the Mw and Mz+1 of the specific (meth)acrylic polymer are calculated in terms of standard polystyrene.
[0025] When there are Ni polymers each having a molecular weight Mi, Mw and Mz+1 are calculated by the following formula. Mw = Σ(Mi 2 ×Ni) / Σ(Mi×Ni) Mz+1=Σ(Mi 4 ×Ni) / Σ(Mi 3 ×Ni)
[0026] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL [Tosoh Corporation] 4 bottles used Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min
[0027] The Mw and Mz+1 of the (meth)acrylic polymer can be adjusted to desired values by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, etc. when polymerizing the monomer. Mz+1 / Mw can be adjusted by controlling the polymerization reaction of the monomers. For example, Mz+1 / Mw can be adjusted by first polymerizing some of the monomers to synthesize a high molecular weight polymer, and then polymerizing the remaining monomers to synthesize a low molecular weight polymer. A specific example is a method in which some of the monomers are polymerized at a relatively low temperature (e.g., 50°C to 70°C) using a polymerization initiator that is an organic peroxide, and then the remaining monomers are polymerized at a relatively high temperature (e.g., 85°C to 95°C) using a polymerization initiator that is an azo compound. In addition, Mz+1 / Mw can be adjusted by using a polyfunctional monomer as a monomer. For example, when a monomer is polymerized, a small amount of a high molecular weight polymer can be synthesized by adding a small amount of a polyfunctional monomer as a monomer. Furthermore, Mz+1 / Mw can also be adjusted, for example, by mixing a (meth)acrylic polymer having a low Mw with a (meth)acrylic polymer having a high Mw.
[0028] The specific (meth)acrylic polymer may be a homopolymer or a copolymer, and is not particularly limited. The specific (meth)acrylic polymer preferably has at least one of a hydroxyl group and a carboxy group, and more preferably has both a hydroxyl group and a carboxy group. When the specific (meth)acrylic polymer has at least one of a hydroxyl group and a carboxy group, for example, when the (meth)acrylic polymer composition of the present disclosure is used as a pressure-sensitive adhesive, there is a tendency that the adhesive strength can be easily adjusted.
[0029] The specific (meth)acrylic polymer may be a polymer having only hydroxyl groups, of hydroxyl groups and carboxy groups, a polymer having only carboxy groups, a polymer having both hydroxyl groups and carboxy groups, or a polymer having neither hydroxyl groups nor carboxy groups. The specific (meth)acrylic polymer having at least one of a hydroxyl group and a carboxyl group may be, for example, a homopolymer of a (meth)acrylic monomer having at least one of a hydroxyl group and a carboxyl group, or may be a homopolymer of a (meth)acrylic monomer having neither a hydroxyl group nor a carboxyl group, into which at least one of a hydroxyl group and a carboxyl group has been introduced by substitution, or may be a copolymer of a (meth)acrylic monomer having at least one of a hydroxyl group and a carboxyl group, or may be a copolymer of a (meth)acrylic monomer having at least one of a hydroxyl group and a carboxyl group and a monomer other than the (meth)acrylic monomer having neither a hydroxyl group nor a carboxyl group, or may be a copolymer of a monomer other than the (meth)acrylic monomer having at least one of a hydroxyl group and a carboxyl group and a (meth)acrylic monomer having neither a hydroxyl group nor a carboxyl group. A preferred embodiment of the specific (meth)acrylic polymer is an embodiment in which the specific (meth)acrylic polymer has at least one of a hydroxyl group and a carboxy group by including at least one of a structural unit derived from a monomer having a hydroxyl group and a structural unit derived from a monomer having a carboxy group, as described below.
[0030] The structural unit of the specific (meth)acrylic polymer will now be described in detail.
[0031] -Structural unit derived from (meth)acrylic acid alkyl ester monomer- The specific (meth)acrylic polymer preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. For example, when the (meth)acrylic polymer composition of the present disclosure is used as a pressure-sensitive adhesive, the structural units derived from the (meth)acrylic acid alkyl ester monomer contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer formed.
[0032] In the present disclosure, the term "structural unit derived from a (meth)acrylic acid alkyl ester monomer" refers to a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer. In addition, the "(meth)acrylic acid alkyl ester monomer" in the present disclosure does not include a monomer corresponding to a monomer having a hydroxyl group described below and a monomer corresponding to a monomer having a carboxy group described below.
[0033] The type of the (meth)acrylic acid alkyl ester monomer is not particularly limited. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The (meth)acrylic acid alkyl ester monomer may be a methacrylic acid alkyl ester monomer or an acrylic acid alkyl ester monomer. However, for example, from the viewpoint of good copolymerizability with other monomers, an acrylic acid alkyl ester monomer is preferable.
[0034] The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.
[0035] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. The (meth)acrylic acid alkyl ester monomer is preferably at least one selected from n-butyl acrylate (n-BA) and 2-ethylhexyl acrylate (2EHA).
[0036] When the specific (meth)acrylic polymer contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the specific (meth)acrylic polymer may contain only one type of structural unit derived from the (meth)acrylic acid alkyl ester monomer, or may contain two or more types of structural units derived from the (meth)acrylic acid alkyl ester monomer.
[0037] When the specific (meth)acrylic polymer contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer is not particularly limited, but for example, it is preferably 50 mass% or more, more preferably 50 mass% to 99.9 mass%, even more preferably 60 mass% to 99.8 mass%, and particularly preferably 70 mass% to 99.7 mass%, relative to all structural units of the specific (meth)acrylic polymer. Here, the content of the structural units derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic polymer being 50 mass% or more relative to the total structural units of the specific (meth)acrylic polymer means that the structural units derived from the (meth)acrylic acid alkyl ester monomer are contained as the main component of the structural units constituting the specific (meth)acrylic polymer.
[0038] -Structural unit derived from a monomer having a hydroxyl group- The specific (meth)acrylic polymer preferably contains a structural unit derived from a monomer having a hydroxyl group. In the present disclosure, a "structural unit derived from a monomer having a hydroxyl group" refers to a structural unit formed by addition polymerization of a monomer having a hydroxyl group.
[0039] An example of a monomer having a hydroxyl group is a monomer having at least one hydroxyl group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0040] The type of the monomer having a hydroxyl group is not particularly limited. Specific examples of monomers having a hydroxyl group include 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, and 1,1-dimethyl-3-hydroxybutyl (meth)acrylate. butyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. As the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl(meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with crosslinking agents (particularly isocyanate-based crosslinking agents), hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and at least one selected from 2-hydroxyethyl acrylate (2HEA) and 4-hydroxybutyl acrylate (4HBA) is particularly preferred.
[0041] When the specific (meth)acrylic polymer contains a structural unit derived from a monomer having a hydroxyl group, the specific (meth)acrylic polymer may contain only one type of structural unit derived from a monomer having a hydroxyl group, or may contain two or more types of structural units derived from a monomer having a hydroxyl group.
[0042] When the specific (meth)acrylic polymer contains a structural unit derived from a monomer having a hydroxyl group, the content of the structural unit derived from the monomer having a hydroxyl group is not particularly limited, but is, for example, preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 8% by mass, and further preferably 1% by mass to 6% by mass, relative to all structural units of the specific (meth)acrylic polymer. The content of structural units derived from monomers having a hydroxyl group in the specific (meth)acrylic polymer being 0.1 mass% or more relative to the total structural units of the specific (meth)acrylic polymer means that the specific (meth)acrylic polymer actively contains structural units derived from monomers having a hydroxyl group. When the content of the structural units derived from the monomer having a hydroxyl group in the specific (meth)acrylic polymer is 10 mass% or less based on the total structural units of the specific (meth)acrylic polymer, the reaction with the crosslinking agent does not proceed excessively, and an increase in the viscosity of the (meth)acrylic polymer composition tends to be suppressed.
[0043] -Structural unit derived from a monomer having a carboxy group- The specific (meth)acrylic polymer preferably contains a structural unit derived from a monomer having a carboxy group. In the present disclosure, a "structural unit derived from a monomer having a carboxy group" refers to a structural unit formed by addition polymerization of a monomer having a carboxy group.
[0044] An example of a monomer having a carboxy group is a monomer having at least one carboxy group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0045] The type of the monomer having a carboxy group is not particularly limited. Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,Ma Examples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate. As the monomer having a carboxy group, for example, acrylic acid (AA) is preferred from the viewpoint of good reactivity with a crosslinking agent (particularly, an isocyanate-based crosslinking agent).
[0046] When the specific (meth)acrylic polymer contains a structural unit derived from a monomer having a carboxy group, the specific (meth)acrylic polymer may contain only one type of structural unit derived from a monomer having a carboxy group, or may contain two or more types of structural units derived from a monomer having a carboxy group.
[0047] When the specific (meth)acrylic polymer contains a structural unit derived from a monomer having a carboxy group, the content of the structural unit derived from the monomer having a carboxy group is not particularly limited, but is, for example, preferably 0.1 mass % to 10 mass %, more preferably 0.2 mass % to 8 mass %, and even more preferably 0.3 mass % to 5 mass %, relative to all structural units of the specific (meth)acrylic polymer. The content of structural units derived from monomers having a carboxy group in the specific (meth)acrylic polymer being 0.1 mass% or more relative to the total structural units of the specific (meth)acrylic polymer means that the specific (meth)acrylic polymer actively contains structural units derived from monomers having a carboxy group. When the content of the structural units derived from the monomer having a carboxy group in the specific (meth)acrylic polymer is 10 mass% or less based on the total structural units of the specific (meth)acrylic polymer, the reaction with the crosslinking agent does not proceed excessively, and an increase in the viscosity of the (meth)acrylic polymer composition tends to be suppressed.
[0048] -Other building blocks- The specific (meth)acrylic polymer may contain, as necessary, structural units other than the structural units described above (so-called other structural units) within the scope that does not impair the effects of the (meth)acrylic polymer composition of the present disclosure.
[0049] Specific examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate and vinyl versatate, and 1,6-hexanediol diacrylate. Also included are various derivatives of these monomers.
[0050] When the specific (meth)acrylic polymer contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.
[0051] When the specific (meth)acrylic polymer contains other structural units, the content of the other structural units is not particularly limited and can be appropriately set depending on the purpose.
[0052] <Content of specific (meth)acrylic polymer> The content of the specific (meth)acrylic polymer in the (meth)acrylic polymer composition of the present disclosure is not particularly limited, but for example, it is preferably 80% by mass to 100% by mass, more preferably 85% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and particularly preferably 95% by mass to 100% by mass, relative to the total solid content in the (meth)acrylic polymer composition.
[0053] <Method of producing specific (meth)acrylic polymer> The method for producing the specific (meth)acrylic polymer is not particularly limited. The method for adjusting Mw, Mz+1, and Mz+1 / Mw of the specific (meth)acrylic polymer has been described above, and therefore the description thereof will be omitted here. The specific (meth)acrylic polymer can basically be produced by polymerizing the above-mentioned monomers using a known polymerization method, such as a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As the polymerization method, the solution polymerization method is preferred in that the processing step is relatively simple and can be carried out in a short time when preparing the (meth)acrylic polymer composition of the present disclosure after production.
[0054] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and reacted by heating for several hours with stirring at the reflux temperature of the organic solvent. In this case, at least a part of the organic solvent, the monomer, the polymerization initiator, and / or the chain transfer agent may be added successively.
[0055] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic or alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds.
[0056] More specifically, examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirit, petroleum naphtha, and turpentine oil; ester compounds such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl acetate, and the like. Examples of the alcohol compounds include ketones, ketone compounds represented by methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.
[0057] In producing the specific (meth)acrylic polymer, it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction, such as an aromatic hydrocarbon compound, an ester compound, or a ketone compound. In particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the specific (meth)acrylic polymer, ease of polymerization reaction, and the like.
[0058] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.
[0059] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the specific (meth)acrylic polymer, an organic peroxide or an azo compound may be used as a polymerization initiator. Since the organic peroxide easily causes a graft reaction during the polymerization reaction, and the azo compound does not easily cause a graft reaction during the polymerization reaction, it is advisable to select an appropriate initiator according to the purpose.
[0060] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.
[0061] The amount of the polymerization initiator used is not particularly limited, and is appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.
[0062] In producing the specific (meth)acrylic polymer, a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds such as α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds such as p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives such as benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives such as tributylborane, carbon tetrabromide, ... Examples of the halogenated hydrocarbon compounds include carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene, aldehyde compounds such as chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds such as thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds such as pinene and terpinolene.
[0063] When a chain transfer agent is used in producing the specific (meth)acrylic polymer, the amount of the chain transfer agent used is not particularly limited and is appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.
[0064] The polymerization temperature is not particularly limited and is appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.
[0065] [Organic Solvent] The (meth)acrylic polymer composition of the present disclosure contains an organic solvent. The type of organic solvent is not particularly limited. Examples of the organic solvent include aromatic hydrocarbon compounds, aliphatic or alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds.
[0066] Specific examples of aromatic hydrocarbon compounds include benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha. Specific examples of aliphatic or alicyclic hydrocarbon compounds include n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirits, petroleum naphtha, and turpentine oil.
[0067] Specific examples of the ester compound include ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate. Specific examples of ketone compounds include acetone, methyl ethyl ketone, methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone.
[0068] Specific examples of glycol ether compounds include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether. Specific examples of the alcohol compound include methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.
[0069] The organic solvent contained in the (meth)acrylic polymer composition of the present disclosure is preferably the same as the organic solvent used in the polymerization reaction of the specific (meth)acrylic polymer, for example, from the viewpoint of facilitating the preparation of the (meth)acrylic polymer composition.
[0070] The (meth)acrylic polymer composition of the present disclosure may contain only one type of organic solvent, or may contain two or more types.
[0071] The content of the organic solvent in the (meth)acrylic polymer composition of the present disclosure is not particularly limited, but for example, relative to the total mass of the (meth)acrylic polymer composition, is preferably 10 mass% to 60 mass%, more preferably 20 mass% to 60 mass%, even more preferably 20 mass% to 50 mass%, and particularly preferably 30 mass% to 50 mass%.
[0072] [Crosslinking Agent] The (meth)acrylic polymer composition of the present disclosure preferably contains a crosslinking agent. When the (meth)acrylic polymer composition of the present disclosure contains a crosslinking agent, it tends to be possible to form a film with better processability. In addition, for example, when the (meth)acrylic polymer composition of the present disclosure is used as an adhesive, it is possible to form an adhesive layer with better processability, and when cutting an adhesive sheet having the adhesive layer, the adhesive layer tends to be less likely to adhere to a cutting blade.
[0073] The type of crosslinking agent is not particularly limited. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and a metal chelate-based crosslinking agent.
[0074] In this disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound). The term "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (so-called bifunctional or higher epoxy compound). The term "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent.
[0075] The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.
[0076] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2030", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).
[0077] The type of the epoxy crosslinking agent is not particularly limited. Epoxy crosslinking agents include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol Examples of suitable glycidyl ethers include glycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether, tetraglycidyl ether,
[0078] As the epoxy-based crosslinking agent, a commercially available product can be used. Examples of commercially available epoxy crosslinking agents include "TETRAD (registered trademark)-X" and "TETRAD (registered trademark)-C" (both manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0079] The type of the metal chelate crosslinking agent is not particularly limited. Examples of the metal chelate crosslinking agent include aluminum chelate compounds such as aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum tris(ethylacetoacetate), and aluminum tris(acetylacetonate), titanium chelate compounds, zirconium chelate compounds, and cobalt chelate compounds.
[0080] As the metal chelate crosslinking agent, commercially available products can be used. Examples of commercially available metal chelate crosslinking agents include Aluminum Chelate A (trade name: aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals Co., Ltd.), Aluminum Chelate D (trade name: aluminum monoacetylacetonate bis(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.), and ALCH-TR (trade name: aluminum tris(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.).
[0081] When the (meth)acrylic polymer composition of the present disclosure contains a crosslinking agent, it may contain only one type of crosslinking agent, or may contain two or more types of crosslinking agents.
[0082] When the (meth)acrylic polymer composition of the present disclosure contains a crosslinking agent, the content of the crosslinking agent is not particularly limited, but is, for example, preferably 0.01 parts by mass to 5 parts by mass, more preferably 0.1 parts by mass to 5 parts by mass, and even more preferably 0.1 parts by mass to 3 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic polymer. The content of the crosslinking agent in the (meth)acrylic polymer composition of the present disclosure being 0.01 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic polymer means that the (meth)acrylic polymer composition of the present disclosure actively contains a crosslinking agent. When the content of the crosslinking agent in the (meth)acrylic polymer composition of the present disclosure is 5 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic polymer, for example, when the (meth)acrylic polymer composition of the present disclosure is used as a pressure-sensitive adhesive, there is a tendency that a pressure-sensitive adhesive layer exhibiting stronger adhesive strength can be formed.
[0083] [Other ingredients] The (meth)acrylic polymer composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, within the scope that does not impair the effects of the composition. Other components include various additives such as crosslinking catalysts, silane coupling agents, surfactants (e.g., polyethylene glycol chain-containing compounds), release regulators, tackifiers, antioxidants, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.
[0084] When the (meth)acrylic polymer composition of the present disclosure contains other components, the contents of the other components can be appropriately set within a range that does not impair the effects of the (meth)acrylic polymer composition of the present disclosure.
[0085] <<Solids concentration of (meth)acrylic polymer composition>> The solids concentration of the (meth)acrylic polymer composition of the present disclosure is not particularly limited, but is preferably, for example, 40% by mass to 90% by mass. When the solid content concentration of the (meth)acrylic polymer composition of the present disclosure is 40% by mass or more, the concentration of the organic solvent is relatively lower, so that a more environmentally friendly (meth)acrylic polymer composition can be realized. From this viewpoint, the solid content concentration of the (meth)acrylic polymer composition of the present disclosure is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more. When the solid content concentration of the (meth)acrylic polymer composition of the present disclosure is 90% by mass or less, the (meth)acrylic polymer composition tends to be easier to prepare. From this viewpoint, the solid content concentration of the (meth)acrylic polymer composition of the present disclosure is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.
[0086] <<Viscosity of (meth)acrylic polymer composition>> The viscosity of the (meth)acrylic polymer composition is not particularly limited, but from the viewpoint of ease of production, for example, it is preferably from 100 mPa / s to 20,000 mPa / s, more preferably from 500 mPa / s to 15,000 mPa / s, even more preferably from 700 mPa / s to 12,000 mPa / s, and particularly preferably from 1,000 mPa / s to 10,000 mPa / s. The viscosity of the (meth)acrylic polymer composition is a value measured using a BH type viscometer after leaving the composition to stand for 3 hours in an environment at an ambient temperature of 25° C. As the BH type viscometer, for example, a BH type viscometer manufactured by Toki Sangyo Co., Ltd. can be suitably used.
[0087] <<Uses of (meth)acrylic polymer compositions>> The use of the (meth)acrylic polymer composition of the present disclosure is not particularly limited. The (meth)acrylic polymer composition of the present disclosure exhibits excellent coatability even when the solid content concentration is high, and can form a film with excellent processability, and therefore can be preferably used, for example, as a paint, ink, binder, and adhesive. Among these, the (meth)acrylic polymer composition of the present disclosure can be particularly preferably used as an adhesive. When the (meth)acrylic polymer composition of the present disclosure is used as an adhesive, a film having excellent processability, i.e., an adhesive layer, can be formed. For example, when an adhesive sheet having an adhesive layer is processed, adhesion of adhesive substances derived from the adhesive layer to a cutting blade is suppressed, and as a result, it is expected that a decrease in productivity caused by a troublesome operation such as cleaning of the cutting blade can be suppressed. In addition, when the (meth)acrylic polymer composition of the present disclosure is used as an adhesive, an adhesive layer exhibiting good adhesive strength can be formed. In this respect, the (meth)acrylic polymer composition of the present disclosure is suitable as an adhesive. Furthermore, the (meth)acrylic polymer composition of the present disclosure can form a film having excellent transparency, and is suitable as, for example, a binder and adhesive used in optical members.
[0088] [Adhesive sheet] The pressure-sensitive adhesive sheet of the present disclosure includes a pressure-sensitive adhesive layer formed from the (meth)acrylic polymer composition of the present disclosure. The pressure-sensitive adhesive layer is a cured product of the (meth)acrylic polymer composition. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore the occurrence of streaks due to poor coating is suppressed, resulting in a good appearance. In addition, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore has excellent processability. Therefore, in the pressure-sensitive adhesive sheet of the present disclosure, adhesive substances derived from the pressure-sensitive adhesive layer are unlikely to adhere to the cutting blade during processing, and it is expected that the decrease in productivity caused by complicated work such as cleaning the cutting blade can be suppressed. Furthermore, the pressure-sensitive adhesive layer provided in the pressure-sensitive adhesive sheet of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore exhibits good adhesive strength. Furthermore, the pressure-sensitive adhesive layer provided in the pressure-sensitive adhesive sheet of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore has excellent transparency.
[0089] The pressure-sensitive adhesive sheet of the present disclosure may be a substrate-free pressure-sensitive adhesive sheet that does not have a substrate, or a substrate-containing pressure-sensitive adhesive sheet that has a pressure-sensitive adhesive layer on at least one surface of a substrate. In the pressure-sensitive adhesive sheet of the present disclosure, the exposed surface of the pressure-sensitive adhesive layer may be protected by a release film.
[0090] The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). Examples of the resin film include polyester films such as polyethylene terephthalate (PET) films. Examples of the release agent include silicone-based release agents (e.g., silicone), wax-based release agents (e.g., paraffin wax), and fluorine-based release agents (e.g., fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive sheet is put to practical use, and is peeled off at the time of use.
[0091] The thickness of the pressure-sensitive adhesive layer is not particularly limited and can be appropriately set depending on, for example, the adhesive strength required for the pressure-sensitive adhesive sheet, the material of the adherend, the shape of the adherend, and the surface roughness of the adherend. The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is generally from 1 μm to 100 μm, preferably from 5 μm to 50 μm, and more preferably from 10 μm to 30 μm.
[0092] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by the following method. The arithmetic mean value of the thicknesses of the adhesive layer measured at 10 randomly selected points in the thickness direction of the adhesive layer is calculated, and the obtained value is regarded as the average thickness of the adhesive layer. The thickness of the adhesive layer is measured using a film thickness meter.
[0093] When the pressure-sensitive adhesive sheet of the present disclosure includes a substrate, the substrate is not particularly limited. Examples of the substrate include films containing resins such as polyester-based resins (e.g., polyethylene terephthalate (PET)), acetate-based resins (e.g., triacetyl cellulose resins), polyethersulfone-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyolefin-based resins (e.g., polyethylene and polypropylene), acrylic resins, vinyl chloride-based resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.
[0094] The surface of the substrate on which the adhesive layer is provided may be subjected to a surface treatment such as corona discharge treatment or plasma discharge treatment (so-called adhesion enhancing treatment) in order to improve adhesion between the substrate and the adhesive layer.
[0095] The substrate may contain various additives, such as plasticizers, colorants (eg, dyes and pigments), heat stabilizers, light stabilizers, antistatic agents, flame retardants, antioxidants, and the like. The substrate may be partially or entirely patterned.
[0096] The thickness of the substrate is not particularly limited. The thickness of the substrate is generally from 10 μm to 500 μm, preferably from 20 μm to 300 μm, and more preferably from 25 μm to 200 μm.
[0097] "Substrate thickness" in this disclosure means the average thickness of the substrate. The average thickness of the substrate is a value measured by a method conforming to the above-mentioned method for measuring the average thickness of the pressure-sensitive adhesive layer.
[0098] The adherend to which the pressure-sensitive adhesive sheet of the present disclosure is applied is not particularly limited. Examples of materials for the adherend of the pressure-sensitive adhesive sheet of the present disclosure include resin, glass, stainless steel, copper, and the like. Examples of the resin include polyolefin resins (eg, polyethylene and polypropylene), acrylic resins, polyester resins (eg, polyethylene terephthalate (PET)), polyimide resins, and triacetyl cellulose resins.
[0099] [How to make adhesive sheets] The pressure-sensitive adhesive sheet of the present disclosure can be produced by known methods. The pressure-sensitive adhesive sheet of the present disclosure can be produced, for example, by the following method. In the case of a substrate-free type adhesive sheet, first, the (meth)acrylic polymer composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. Then, the formed coating film is dried to form an adhesive film on the release film. Next, the exposed surface of the formed adhesive film is laminated and attached to the easy-release treated surface of a separately prepared release film, and then cured to produce a substrate-free type adhesive sheet having a laminated structure of release film / adhesive layer / release film.
[0100] In the case of a substrate-type adhesive sheet, first, the (meth)acrylic polymer composition of the present disclosure is applied to an easily adhesive treated surface of the substrate to form a coating film on the substrate. Then, the formed coating film is dried to form an adhesive film on the substrate. Next, the exposed surface of the formed adhesive film is laminated on the easily peelable treated surface of a release film, and then cured to produce a substrate-type adhesive sheet having a laminated structure of release film / adhesive layer / substrate.
[0101] As another method, for example, the following method can be mentioned. The (meth)acrylic polymer composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then laminated to the easy-adhesion treated surface of a substrate, and then cured to produce a substrate-type adhesive sheet having a laminated structure of substrate / adhesive layer / release film.
[0102] The method for applying the (meth)acrylic polymer composition is not particularly limited. Examples of methods for applying the (meth)acrylic polymer composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the (meth)acrylic polymer composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the pressure-sensitive adhesive layer to be formed.
[0103] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 seconds to 3 minutes.
[0104] The curing is carried out, for example, for three days in an environment with an atmospheric temperature of 20° C. to 35° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH).
[0105] [Optical components] The optical member of the present disclosure is an optical member having a pressure-sensitive adhesive layer formed from the (meth)acrylic polymer composition of the present disclosure. The pressure-sensitive adhesive layer of the optical member of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore the occurrence of streaks due to poor coating is suppressed, resulting in a good appearance. In addition, the pressure-sensitive adhesive layer of the optical member of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure, and therefore has excellent processability. Therefore, in the optical member of the present disclosure, the adhesive substance derived from the pressure-sensitive adhesive layer is unlikely to adhere to the cutting blade during processing, and it is expected that the decrease in productivity caused by the troublesome work of cleaning the cutting blade can be suppressed. In addition, the pressure-sensitive adhesive layer included in the optical member of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore exhibits good adhesive strength. In addition, the pressure-sensitive adhesive layer included in the optical member of the present disclosure is formed from the (meth)acrylic polymer composition of the present disclosure described above, and therefore has excellent transparency.
[0106] The optical member is not particularly limited, and examples thereof include members constituting devices such as image display devices and input devices (so-called optical devices) and members used in these devices. Specific examples of optical components include polarizing plates, AG (Anti-Glare) polarizing plates, wave plates, retardation plates including 1 / 2, 1 / 4 and other wave plates, viewing angle compensation films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflection films, transparent conductive films such as ITO (Indium-Tin Oxide) films, prism sheets, lens sheets, and diffusion plates. Examples of materials for optical components include polyester-based resins, acetate-based resins (e.g., triacetyl cellulose resins), polyethersulfone-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyolefin-based resins (e.g., polyethylene and polypropylene), acrylic-based resins, vinyl chloride-based resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins. EXAMPLES
[0107] The (meth)acrylic polymer composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.
[0108] [Production of (meth)acrylic polymer composition] [Manufacturing example A-1] In a reaction vessel equipped with a thermometer, a stirrer, and a reflux condenser, 13.0 parts by mass of ethyl acetate [organic solvent] was placed. Next, in another vessel, 98.2 parts by mass of n-butyl acrylate [n-BA; acrylic acid alkyl ester monomer], 1.5 parts by mass of 2-hydroxyethyl acrylate [2HEA; monomer having a hydroxyl group], and 0.3 parts by mass of acrylic acid [AA; monomer having a carboxyl group] were placed and mixed to prepare a monomer mixture. Of this monomer mixture, 5.0% by mass was placed in the reaction vessel. Next, while stirring the contents in the reaction vessel, the temperature of the contents was raised to 85°C. Next, a mixture of 10.0 parts by mass of ethyl acetate and 0.002 parts by mass of t-butyl peroxypivalate [trade name: Perbutyl (registered trademark) PV, manufactured by NOF Corp., polymerization initiator] was successively dropped into the reaction vessel, and the reactants in the reaction vessel were reacted for 1 hour to obtain a reaction product (a1). Next, the remaining monomer mixture (95.0 mass%) and a liquid prepared by dissolving 3.0 mass parts of 2,2'-azobisisobutyronitrile (AIBN; polymerization initiator) in 10.0 mass parts of ethyl acetate were successively added dropwise to the reaction product (a1) in the reaction vessel over a period of 2 hours to react the reactants in the reaction vessel, and after the completion of the dropping, the reaction was continued for another 2 hours to obtain reaction product (a2). The obtained reaction product (a2) was diluted with ethyl acetate to a solid content concentration of 75 mass%, to obtain (meth)acrylic polymer composition A-1. Hereinafter, the (meth)acrylic polymer contained in the (meth)acrylic polymer composition A-1 will be referred to as "(meth)acrylic polymer A-1."
[0109] The "solid content" here refers to the (meth)acrylic polymer A-1, and the "solid content concentration" refers to the mass proportion of the (meth)acrylic polymer A-1 in the (meth)acrylic polymer composition A-1. The same applies to the following (meth)acrylic polymer compositions A-2 to A-20.
[0110] [Production Examples A-2 to A-4, A-9, A-17, and A-18] In Production Examples A-2 to A-4, A-9, A-17, and A-18, the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the (meth)acrylic polymer were adjusted to the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) shown in Table 1 by adjusting the proportion of the monomer mixture used at the beginning of the reaction, the amount of the polymerization initiator used, and the reaction time. Except for this, the same operation as in Production Example A-1 was performed to obtain (meth)acrylic polymer compositions A-2 to A-4, A-9, A-17, and A-18 having a solid content concentration of 65 mass%. Hereinafter, the (meth)acrylic polymers contained in the (meth)acrylic polymer compositions A-2 to A-4, A-9, A-17, and A-18 will be referred to as "(meth)acrylic polymers A-2 to A-4, A-9, A-17, and A-18," respectively.
[0111] [Production Examples A-5 to A-8, A-10, A-11, A-15, and A-20] In Production Examples A-5 to A-8, A-10, A-11, A-15, and A-20, the monomer composition of the (meth)acrylic polymer composition was changed to the monomer composition shown in Table 1, and the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the (meth)acrylic polymer were adjusted to the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) shown in Table 1 by adjusting the proportion of the monomer mixture used at the beginning of the reaction, the amount of the polymerization initiator used, and the reaction time. The same operation as in Production Example A-1 was performed to obtain (meth)acrylic polymer compositions A-5 to A-8, A-10, A-11, A-15, and A-20 having a solid content concentration of 65% by mass. Hereinafter, the (meth)acrylic polymers contained in the (meth)acrylic polymer compositions A-5 to A-8, A-10, A-11, A-15, and A-20 will be referred to as "(meth)acrylic polymers A-5 to A-8, A-10, A-11, A-15, and A-20," respectively.
[0112] [Manufacturing example A-12] In Production Example A-12, the monomer composition of the (meth)acrylic polymer composition was changed to the monomer composition shown in Table 1, and the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the (meth)acrylic polymer were adjusted to the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) shown in Table 1 by adjusting the proportion of the monomer mixture used at the beginning of the reaction, the amount of the polymerization initiator used, and the reaction time. Except for this, the same operation as in Production Example A-1 was performed to obtain a (meth)acrylic polymer composition A-12 having a solid content concentration of 55 mass%. Hereinafter, the (meth)acrylic polymer contained in the (meth)acrylic polymer composition A-12 is referred to as "(meth)acrylic polymer A-12."
[0113] [Manufacturing example A-13] 100 parts by mass (solid content equivalent) of (meth)acrylic polymer composition A-14 described later and 0.5 parts by mass (solid content equivalent) of (meth)acrylic polymer composition A-19 described later were mixed, and then diluted with ethyl acetate to a solid content concentration of 60% by mass to obtain (meth)acrylic polymer composition A-13. Hereinafter, the (meth)acrylic polymer contained in the (meth)acrylic polymer composition A-13 is referred to as "(meth)acrylic polymer A-13."
[0114] [Manufacturing example A-14] In a reaction vessel equipped with a thermometer, a stirrer, and a reflux condenser, 30.0 parts by mass of ethyl acetate [organic solvent] was placed. Next, in another vessel, 65.0 parts by mass of n-butyl acrylate [n-BA; acrylic acid alkyl ester monomer], 33.2 parts by mass of 2-ethylhexyl acrylate [2EHA; acrylic acid alkyl ester monomer], 1.5 parts by mass of 2-hydroxyethyl acrylate [2HEA; monomer having a hydroxyl group], and 0.3 parts by mass of acrylic acid [AA; monomer having a carboxyl group] were placed and mixed to prepare a monomer mixture. Of this monomer mixture, 8.0% by mass was placed in the reaction vessel. Next, 0.6 parts by mass of 2,2'-azobisisobutyronitrile [AIBN; polymerization initiator] was added, and the temperature of the contents in the reaction vessel was raised to 85°C while stirring the contents, to start the initial reaction. After the initial reaction was almost completed, the remaining monomer mixture (92.0 mass%), ethyl acetate (10.0 mass parts) and AIBN (3.0 mass parts) were successively added dropwise over 2 hours to the reaction vessel to react the reactants in the reaction vessel, and after the addition was completed, the reaction was continued for another 2 hours to obtain a reaction product. The reaction product obtained was diluted with ethyl acetate to a solid content of 65 mass%, to obtain (meth)acrylic polymer composition A-14. Hereinafter, the (meth)acrylic polymer contained in the (meth)acrylic polymer composition A-14 is referred to as "(meth)acrylic polymer A-14".
[0115] [Manufacturing example A-16] In Production Example A-16, the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the (meth)acrylic polymer were adjusted to the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) shown in Table 1 by adjusting the proportion of the monomer mixture used at the beginning of the reaction, the amount of the polymerization initiator used, and the reaction time, but the same operation as in Production Example A-14 was performed to obtain a (meth)acrylic polymer composition A-16 having a solid content concentration of 65 mass%. Hereinafter, the (meth)acrylic polymer contained in the (meth)acrylic polymer composition A-16 is referred to as "(meth)acrylic polymer A-16."
[0116] [Manufacturing example A-19] In Production Example A-19, the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the (meth)acrylic polymer were adjusted to the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) shown in Table 1 by adjusting the proportion of the monomer mixture used at the beginning of the reaction, the amount of the polymerization initiator used, and the reaction time, but the same operation as in Production Example A-14 was performed to obtain a (meth)acrylic polymer composition A-19 having a solid content concentration of 24 mass%. Hereinafter, the (meth)acrylic polymer contained in the (meth)acrylic polymer composition A-19 is referred to as "(meth)acrylic polymer A-19".
[0117] Monomer composition (unit: mass%) and weight average molecular weight (Mw) of (meth)acrylic polymers A-1 to A-20 [unit: 10,000 (in the table, "×10 4 z+1 average molecular weight (Mz+1) [unit: 10,000 (in the table, "x 10 4 The z+1 average molecular weight (Mz+1) and the weight average molecular weight (Mw) ratio [Mz+1 / Mw], as well as the solids concentration (unit: mass%) and viscosity (unit: mPa s) of each of the (meth)acrylic polymer compositions A-1 to A-20 are shown in Table 1.
[0118] The weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the (meth)acrylic polymers A-1 to A-20 were measured by the same method as the method for measuring the weight average molecular weight (Mw) and z+1 average molecular weight (Mz+1) of the specific (meth)acrylic polymer described above. The viscosities of the (meth)acrylic polymer compositions A-1 to A-20 were measured by the same method as the above-mentioned method for measuring the viscosity of the (meth)acrylic polymer composition.
[0119] Among the (meth)acrylic polymers A-1 to A-20 contained in the (meth)acrylic polymer compositions A-1 to A-20 obtained above, the (meth)acrylic polymers A-1 to A-8 and A-11 to A-13 correspond to the specific (meth)acrylic polymers in the present disclosure.
[0120] [Table 1]
[0121] Details of each monomer listed in Table 1 are as follows. "n-BA": n-butyl acrylate (acrylic acid alkyl ester monomer) "2EHA": 2-Ethylhexyl acrylate (acrylic acid alkyl ester monomer) "2HEA": 2-hydroxyethyl acrylate (a monomer having a hydroxyl group) "4HBA": 4-hydroxybutyl acrylate (a monomer having a hydroxyl group) "AA": acrylic acid (monomer with a carboxy group) "1,6-HX": 1,6-Hexanediol diacrylate (other monomer)
[0122] In Table 1, the values shown in the column "Monomer composition [mass %]" are all values calculated as solid content. In Table 1, "-" in the monomer composition column means that the monomer in that column is not contained. In Table 1, "weight average molecular weight" is represented as "Mw", "z+1 average molecular weight" is represented as "Mz+1", and "ratio of z+1 average molecular weight (Mz+1) to weight average molecular weight (Mw)" is represented as "Mz+1 / Mw".
[0123] [Preparation of Adhesive Composition] Example 1 133.3 parts by mass of the (meth)acrylic polymer composition A-1 (100 parts by mass as solid content) and 0.5 parts by mass of Sumidur (registered trademark) N-3300 (trade name, trimer of hexamethylene diisocyanate (HMDI), solid content concentration: 100% by mass, manufactured by Sumika Covestro Urethane Co., Ltd.), which is an isocyanate-based crosslinking agent, were thoroughly mixed to obtain a mixture. The obtained mixture was diluted with ethyl acetate so that the solid content concentration became 50% by mass, and the adhesive composition of Example 1 was obtained. The pressure-sensitive adhesive composition of Example 1 obtained as described above is one embodiment of the (meth)acrylic polymer composition of the present disclosure. The same applies to each of the pressure-sensitive adhesive compositions of Examples 1 to 16 below.
[0124] [Examples 2 to 16] The same procedure as in Example 1 was carried out except that the composition and solid content concentration of the pressure-sensitive adhesive composition in Example 1 were changed to those shown in Table 2, to obtain each of the pressure-sensitive adhesive compositions of Examples 2 to 16.
[0125] [Comparative Examples 1 to 8] The same procedure as in Example 1 was carried out except that the composition and solid content concentration of the pressure-sensitive adhesive composition in Example 1 were changed to those shown in Table 3, to obtain each of the pressure-sensitive adhesive compositions of Comparative Examples 1 to 8.
[0126] [Measurement and Evaluation] The following measurements and evaluations were carried out using each of the pressure-sensitive adhesive compositions of Examples 1 to 16 and Comparative Examples 1 to 8. The results are shown in Tables 2 and 3.
[0127] 1. Coatability (1) Paint film formation The coatability of the pressure-sensitive adhesive composition was evaluated using the formation of a coating film as an index. The adhesive composition prepared above was applied to the adhesive treated surface of an easily adhesive treated polyethylene terephthalate (PET) film (trade name: Teijin (registered trademark) Tetoron (registered trademark) film, model number: G2, thickness: 38 μm, manufactured by Teijin Film Solutions Co., Ltd.) at a coating speed of 60 m / min and a thickness of 40 cm, using an applicator (model number: SA-202, manufactured by Tester Sangyo Co., Ltd.) so that the film thickness after drying would be 15 μm. The state of the coating film formed was visually observed from the start to the end of application of the adhesive composition. Evaluation was then performed according to the following evaluation criteria. If the evaluation result was "A" or "B", it was determined that the PSA composition was capable of forming a good coating film even when the solid content was high.
[0128] -Evaluation criteria- A: The coating film was continuous from the start to the end of application of the pressure-sensitive adhesive composition. B: The coating film was continuous from the start to the end of application of the pressure-sensitive adhesive composition, but small repelling occurred at the edge of the coating film. C: The coating film was interrupted between the start and end of application of the pressure-sensitive adhesive composition.
[0129] (2) Coating appearance The coatability of the pressure-sensitive adhesive composition was evaluated using the appearance of the coating film as an index. The same operation as in "(1) Formation of coating film" was carried out to form a coating film, and the formed coating film was visually observed. Then, evaluation was carried out according to the following evaluation criteria. If the evaluation result was "A" or "B", it was determined that the PSA composition was capable of forming a coating film with good appearance even when the solid content was high.
[0130] -Evaluation criteria- A: No streaks were observed on the coating. B: Slight streaks were observed only at the edges of the coating film. C: Streaks were observed throughout the entire coating.
[0131] 2. Processability The processability of the adhesive layer was evaluated using as an index the deformation rate of the adhesive layer when a high stress was applied (so-called creep value). The adhesive composition prepared above was applied to the surface-treated surface of a release film P (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been surface-treated with a silicone-based release treatment agent, so that the film thickness after drying was 100 μm, forming a coating film. The formed coating film was then dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, forming an adhesive film on the release film P. Next, the exposed surface of the adhesive film was placed on the surface-treated surface of a release film Q (trade name: Film Byna (registered trademark) 25E-0010 BD, thickness: 25 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been surface-treated with a separately prepared silicone-based release treatment agent, and the two films were pressed together by passing them through a pressure nip roll, and then left to stand for 3 days in an environment with an atmospheric temperature of 23 ° C. and 50% RH for aging, to prepare an evaluation adhesive sheet. The prepared pressure-sensitive adhesive sheet for evaluation had a laminated structure of release film Q / pressure-sensitive adhesive layer (thickness: 100 μm) / release film P. The adhesive sheet for evaluation prepared above was cut into four pieces of adhesive sheet for evaluation with a size of 25 mm x 150 mm. Next, the release film P and the release film Q were peeled off from the four pieces of adhesive sheet for evaluation prepared [composition: release film Q / adhesive layer (thickness: 100 μm) / release film P], and the surfaces of the adhesive layer were bonded together to form an adhesive layer with a thickness of 400 μm. The formed adhesive layer was cut out to fit a measuring tool PP8 [manufactured by Anton Paar] to prepare a test piece. The deformation rate of the prepared test piece when a stress of 2000 Pa was applied in an environment of an atmospheric temperature of 60°C and 50% RH was measured using a dynamic viscoelasticity measuring device [model number: MCR301] manufactured by Anton Paar as a measuring device, and the obtained value was taken as the creep value (unit: %). Then, evaluation was performed according to the following evaluation criteria. If the evaluation result was "A," "B," or "C," the pressure-sensitive adhesive layer was determined to have excellent processability.
[0132] -Evaluation criteria- A: The creep value was 20% or less. B: Creep value was more than 20% and less than 25%. C: Creep value was more than 25% and less than 30%. D: Creep value was more than 30%.
[0133] 3. Adhesive strength The adhesive composition prepared above was applied to the adhesive treated surface of an easily adhesive treated polyethylene terephthalate (PET) film [trade name: Teijin (registered trademark) Tetron (registered trademark) film, model number: G2, thickness: 38 μm, manufactured by Teijin Film Solutions Co., Ltd.] so that the film thickness after drying was 15 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C and a drying time of 1 minute, forming an adhesive film on the PET film. Next, the exposed surface of the adhesive film was placed on the surface-treated surface of a release film [trade name: Film Vina (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been surface-treated with a separately prepared silicone-based release treatment agent, and the two films were pressed together by passing them through a pressure nip roll, and then left to stand for 3 days in an environment with an atmospheric temperature of 23 ° C and 50% RH to cure, and an evaluation adhesive sheet was prepared. The prepared pressure-sensitive adhesive sheet for evaluation had a laminated structure of release film / pressure-sensitive adhesive layer (thickness: 15 μm) / PET film (substrate). The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece A-1 for evaluation. Next, the release film of the prepared adhesive sheet piece A-1 for evaluation [composition: release film / adhesive layer / PET film (substrate)] was peeled off, and the surface of the adhesive layer exposed by peeling was placed on the surface of a PET film as an adherend [product name: Cosmoshine (registered trademark) A4300, thickness: 250 μm, manufactured by Toyobo Co., Ltd.], and then pressed together using a tabletop laminator to prepare a laminate. The prepared laminate has a laminated structure of PET film (adherend) / adhesive sheet piece A-2 for evaluation [composition: adhesive layer (thickness: 15 μm) / PET film (substrate)]. Next, the prepared laminate was left to stand for 24 hours in an environment with an atmospheric temperature of 23 ° C. and 50% RH to prepare a test piece. For this test piece, the adhesive strength (unit: N / 25 mm) when the evaluation adhesive sheet piece A-2 was peeled off 180° in the long side (150 mm) direction from the PET film (adherend) was measured using a single column type material testing machine (model number: STA-1225) manufactured by A&D Co., Ltd. as the measuring device under conditions of an ambient temperature of 23°C, 50% RH, and a peel speed of 300 mm / min. If the adhesive strength was 0.05 N / 25 mm or more, it was determined that the adhesive layer exhibited good adhesive strength.
[0134] 4.Transparency The adhesive sheet for evaluation prepared in the above "3. Adhesive strength" was cut to a size of 25 mm × 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from this prepared adhesive sheet piece for evaluation to prepare a test piece, and the haze (unit: %) was measured using a haze meter (model number: NDH 5000SP, manufactured by Nippon Denshoku Industries Co., Ltd.). If the haze value was 2.0% or less, it was determined that the pressure-sensitive adhesive layer had excellent transparency.
[0135] [Table 2]
[0136] [Table 3]
[0137] In Tables 2 and 3, the values shown in the "blended amount" column are all values calculated as solid content.
[0138] Details of the crosslinking agents listed in Tables 2 and 3 are as follows. "HMDI" [Product name: Sumidur (registered trademark) N-3300, trimer of hexamethylene diisocyanate (HMDI), solid content concentration: 100% by mass, manufactured by Sumika Covestro Urethane Co., Ltd.] "TDI" (product name: Coronate (registered trademark) L-45E, an adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP), solid content concentration: 45% by mass, manufactured by Tosoh Corporation) "XDI" [Product name: Takenate (registered trademark) D-110N, adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP), solid content concentration: 75% by mass, manufactured by Mitsui Chemicals, Inc.]
[0139] As shown in Table 2, it was confirmed that the pressure-sensitive adhesive compositions of Examples 1 to 16 exhibited excellent coatability even when the solid content concentration was high. It was also confirmed that the pressure-sensitive adhesive compositions of Examples 1 to 16 were capable of forming pressure-sensitive adhesive layers with excellent processability. It was also confirmed that the pressure-sensitive adhesive compositions of Examples 1 to 16 were capable of forming pressure-sensitive adhesive layers exhibiting good adhesive strength. It was also confirmed that the pressure-sensitive adhesive compositions of Examples 1 to 16 were capable of forming pressure-sensitive adhesive layers with excellent transparency. On the other hand, as shown in Table 3, the pressure-sensitive adhesive compositions of Comparative Examples 1 to 8 were confirmed to be inferior to the pressure-sensitive adhesive compositions of the Examples in at least one of the evaluations of coatability and processability when the solid content concentration was high.
Claims
1. a (meth)acrylic polymer having a weight average molecular weight (Mw) of 50,000 to 250,000, a z+1 average molecular weight (Mz+1) of 500,000 to 20 million, and a ratio (Mz+1 / Mw) of the z+1 average molecular weight (Mz+1) to the weight average molecular weight (Mw) of 5.5 or more (excluding the case of including a (meth)acrylic copolymer containing a structural unit derived from a monomer having a hydroxyl group, having a glass transition temperature of -40°C or less, and having a weight average molecular weight in the range of 300,000 to 1,500,000, and a (meth)acrylic copolymer containing a structural unit derived from a monomer having a hydroxyl group, having a glass transition temperature of -10°C or more and 45°C or less, and having a weight average molecular weight in the range of more than 10,000 to 200,000); An organic solvent; A cross-linking agent; Including, the (meth)acrylic polymer comprises a structural unit derived from a (meth)acrylic acid alkyl ester monomer, and at least one structural unit selected from the group consisting of a structural unit derived from a monomer having a hydroxyl group and a structural unit derived from a monomer having a carboxy group, A (meth)acrylic polymer composition having a solids concentration of 40% by mass to 80% by mass.
2. The (meth)acrylic polymer composition according to claim 1 , wherein the crosslinking agent is an isocyanate crosslinking agent.
3. The (meth)acrylic polymer composition according to claim 1 or 2, which is used as a pressure-sensitive adhesive.
4. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the (meth)acrylic polymer composition according to claim 3 .
5. An optical member comprising a pressure-sensitive adhesive layer formed from the (meth)acrylic polymer composition according to claim 3 .
Citation Information
Patent Citations
Piping member
JP2008291183A
Method for producing removable pressure-sensitive adhesive film
JP2010043184A
Acrylic resin solution, acrylic adhesive composition, acrylic adhesive, adhesive sheet, acrylic adhesive for optical element, and optical element with adhesive layer
JP2011246700A
Adhesive and adhesive film using the same
JP2013189601A
Adhesive sheet
JP2018159019A